Association of BMI with Serum Homocysteine in Polycystic Ovarian Syndrome Women - Roshni G. Sadaria; Smita N. Vasava (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Women of reproductive age group are prone for Polycystic ovarian syndrome (PCOS). Recentstudies have shown that hyperhomocysteinemia is a risk factor for cardiovascular diseases. Prevalence ofcardiovascular disease and cardiovascular morbidities in women with PCOS are increased nowadays. Thepurpose of the study is to assess correlation of BMI with serum homocysteine in PCOS females.Materials and Methods: This is done on 50 PCOS patients and 50 voluntary age matched healthy womenwith no menstrual abnormalities as controls. The age group for the cases and controls is 18-35 years. Thestudy was conducted at Biochemistry Department, SBKS MI & RC, Piparia, Vadodara, Gujarat, India.Measurements of BMI and waist circumference were taken. Fasting blood samples were collected forestimation of FBS, Lipid profile and homocysteine. Medcalc software was used for all statistical analysis. Ap-value less than 0.05 (p< 0.05) is considered as statistically significant.Conclusion: Our study has shown significant higher levels of homocysteine in obese PCOS cases whencompared with non-obese PCOS cases. Also, significant higher level of homocysteine and triglyceride areseen in PCOS cases compared to controls. Regular follow up for lipid profile and homocysteine is requiredfor PCOS patients to prevent CVS complications.